Identification of the btuCED polypeptides and evidence for their role in vitamin B12 transport in Escherichia coli. - de Veaux, L C (1986)
Passage of vitamin B12 across the outer and cytoplasmic membranes of Escherichia coli occurs in two steps, each involving independent transport systems. Since the vitamin accumulated in btuC or btuD mutants is readily released from the cell by chase or osmotic shock and does not undergo the usual metabolic conversions, the products of these genes might participate in transport across the cytoplasmic membrane. Mutations in btuC and btuD are complemented by recombinant plasmids carrying a 3,410-base-pair HindIII-HincII DNA fragment. Transposon Tn1000 mutagenesis and subcloning defined the location of these two genes and showed that they are separated by approximately 800 base pairs. The polypeptides elicited by this fragment and its derivatives were identified by using a maxicell system. The apparent molecular weight of the btuC product was approximately 26,000, that of the btuD product was 29,000. Both polypeptides were associated with the cell membrane. Transposon insertions in the region between btuC and btuD, as well as those in the two genes, conferred a deficiency in vitamin B12 utilization and transport when they were crossed onto the chromosome. This region, termed btuE, encoded a 22,000-Mr polypeptide and lesser amounts of a 20,000-Mr species. A portion of the BtuE protein was released from maxicells by osmotic shock or spheroplast formation. The relative production of BtuE and BtuD in response to plasmids carrying transposon insertions suggested that the three genes are arranged in an operon in the order btuC-btuE-btuD and that internal promoters exist since polarity was incomplete. Substantial elevation of transport activity was engendered by plasmids carrying the intact btu region, but not when any of the btu genes was disrupted. The btuCED region thus may encode a transport system for passage of vitamin B12 across the cytoplasmic membrane. This system bears similarities to periplasmic binding protein-dependent transport systems, although the putative periplasmic component is not required for its function.